NARRATIVE THERAPY AND ORGANIZATIONAL CULTURE MANAGEMENT: POSSIBLE ARTICULATIONS - Loureiro, Simone Porto (Seven Editora, 2024)
The word narrative has become popular in recent times. Disseminated by the media, among other contexts, it appears in political analyses and in discussions about fictional works. In addition to its strictly communicational aspects, the narrative element plays a central role in a clinical, therapeutic, psychological and social approach: narrative therapy. The present study aimed to analyze a possible approximation of the use of practices developed in the field of narrative therapy in works focused on the management of organizational culture (a field traditionally more associated with other knowledge, such as organizational psychology and business administration). In this approach, we sought points of discussion and concepts from studies on organizational culture and others derived from narrative practices, originally developed in the field of narrative therapy. Despite the practical and epistemological challenges, the approximation of the knowledge that emerges from these two fields of study is fruitful, rich in possibilities for organizations and for people who experience their professional activities in them or who can benefit from their social impacts. DOI:https://doi.org/10.56238/sevened2024.037-009